2021
DOI: 10.3390/vaccines9040355
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Safety and Efficacy of an Inactivated Marker Vaccine against Bovine alphaherpesvirus 1 (BoHV-1) in Water Buffalo (Bubalus bubalis)

Abstract: Recent studies have explored the seropositivity of Bovine alphaherpesvirus 1 (BoHV-1) in water buffaloes, suggesting the urgency for developing strategies to eradicate the virus involving both cattle and water buffaloes. However, in Europe, the glycoprotein E (gE) deleted marker vaccines against BoHV-1 are commercially available only for the cattle industry. This study, for the first time, evaluated the safety and efficacy of a commercial inactivated gE-deleted marker vaccine in water buffalo. Five animals dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
15
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 28 publications
5
15
2
Order By: Relevance
“…To date, it is known that water buffalo can be infected with bovine alphaherpesvirus 1 (BoHV-1) and bubaline alphaherpesvirus 1 (BuHV-1) [ 2 , 3 ]. These two viruses belong to the viral family Herpesviridae [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, it is known that water buffalo can be infected with bovine alphaherpesvirus 1 (BoHV-1) and bubaline alphaherpesvirus 1 (BuHV-1) [ 2 , 3 ]. These two viruses belong to the viral family Herpesviridae [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, no commercial vaccine has been developed to date for the control of BuHV-1. Furthermore, using the single BoHV-1 gE-deleted marker vaccine to control BuHV-1 in water buffaloes has been shown to result in cross-protection against BuHV-1 [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the results obtained from gB-ELISA tests, in general, indicate the presence of specific antibodies against gB of BoHV-1 [ 25 ]; in some cases, this positivity could originate from other herpesviruses such as Bovine alphaherpesvirus 2 [ 26 , 27 , 28 ]. It has also been shown that positive results from gE-ELISAs in cattle or buffalo could be influenced by a previously circulating wild-type BoHV-1 in the herd [ 29 , 30 ]. In addition, to improve the sensitivity of blocking gE-ELISAs, some methods use milk-concentrating protocols [ 21 , 23 , 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the IDEXX IBR gE Ab test and IDEXX IBR gB X3 Ab test were used to detect glycoprotein B (gB) or glycoprotein E (gE) of BoHV-1. These tests, developed for BoHV-1, cross-react with the glycoproteins (gB -gE) of BuHV-1 [ 16 ].…”
Section: Methodsmentioning
confidence: 99%